Analisa Dan Perancangan Sistem Informasi Sekolah SMK Taman Siswa Padang Tualang Dengan Metode Agile Berbasis Web - Cinta Pandia; Raheliya Br Ginting; Siti Br Jamilah (Institut Teknologi dan Bisnis Indonesia, 2025)
The existing academic system at Taman Siswa Private Vocational School Padang Tualang already uses computerized systems such as Microsoft Excel and Microsoft Word which are used by Administration employees to manage school reports and data. However, this system has shortcomings such as making it difficult to search for data, the possibility of data being lost, and also when providing school information it is still done by interacting with the community to provide an overview of the school's background. Therefore, a school information system website is needed that can display the school profile, school facilities, announcements, organizational structure, and can input student data, teacher data, and lesson schedules. The data collection methods used in this research are observation, interviews, documentation and literature study. The method used in the system is the agile method and to design the system process design it is created using UML (Unified Modeling Language). This research resulted in an information system design at the Taman Siswa Padang Tualang Private Vocational School. In creating this School Information System the author used the PHP and MySQL programming languages as databases. From this research process, a school website was produced which succeeded in increasing the efficiency of teachers, students and the community regarding information related to the Padang Tualang Taman Siswa Vocational school.